Switch from intravenous or intramuscular to subcutaneous hepatitis B immunoglobulin: effect on quality of life after liver transplantation - Riccardo Volpes (Health and Quality of Life Outcomes, 2020)
Abstract Background Hepatitis B immunoglobulin (HBIG) therapy is available in intravenous (IV) or intra-muscular (IM) formulations. Recently, a subcutaneous (SC) formulation was introduced. This study evaluated changes in quality of life when liver transplant (LT) recipients were switched from IV or IM HBIG to the SC formulation. Methods This multicentre, observational study involved adults who had undergone LT at least 1 year prior to study entry. Quality of life was evaluated using the ITaLi-Q questionnaire, assessing the impact of HBIG therapy on daily activities and patient satisfaction, and the SF-36 Health Survey. Patients completed the questionnaires prior to switching from IV or IM HBIG to SC HBIG and 6 months later. Results Eighty-six patients were enrolled; before the switch, 68.6% were receiving IM HBIG and 31.4% IV HBIG. After 6 months, significant improvements in 7 of the 8 ITaLi-Q domains were found, particularly side effects, need for support to adhere to the therapy and satisfaction with the HBIG therapy. Significant improvements in several SF-36 domains were documented, including physical functioning, physical and emotional role limitations, pain, social functioning, physical and mental summary scores. Conclusions The SC route of administration reduces side effects and their interference with daily life, ameliorates negative feelings, and increases patient autonomy.